Handbook of enology = (John Wiley, 2006)
This two volume set serves as both a text and reference book for students and practitioners interested and working in the field of winemaking. These books features new scientific and technological results to reflect the most up-to-date knowledge in winemaking. The handbook discusses the scientific basics and technological problems of winemaking and the resulting consequences for the practitioner, providing an authoritative and complete reference manual for the winemaker, and an in-depth textbook for the student.